Analisis Tingkat Bahaya Karhutla (Kebakaran Hutan dan Lahan) di Kabupaten Ogan Ilir Provinsi Sumatera Selatan - Budi Utomo; Boby Agus Yusmiono; Aldo Panji Prasetya; Mini Julita; Mega Kusuma Putri (Department of Urban and Regional Planning, Diponegoro University, 2022)
Forest and land fires are disasters that occur every year in Ogan Ilir Regency. The largest forest and land fire disaster in this district was in 2015. Still, this disaster was repeated in the following year, from 2016 to 2020. This research is one of the efforts to mitigate forest and land fires to reduce the fire risk. This study aims to analyze the level of danger caused by forest fires and land. The method used in this study is a quantitative descriptive method using overlay analysis. This research is located in Ogan Ilir Regency because Ogan Ilir Regency is one of the regencies in the Sumatra Province of Sumatra, which often occurs in fires. The measurement of the hazard level of forest and land fires (forest and land fires) uses several parameters, including a map of land cover types in Ogan Ilir Regency, a rainfall map in Ogan Ilir Regency, and a map of soil types in Ogan Ilir Regency. The study's results show that the level of danger of forest and land fires in Ogan Ilir Regency is classified into three levels. The first level is high, with an area of 204,51 km² or 10,11% of the total area. Then the medium level has an area of 1182,06 Km² or 58,43% of the entire area. Then the last level is the low level which has an area of 363,45 Km² or about 31,46% of the total area of Ogan Ilir Regency. Research on the level of danger of a disaster becomes essential because it is auxiliary information to determine and analyze which locations are prone to a disaster.